Compute (1+i)(2+i)(3+i).

I know that i^2 is equal to -1. So i tried just solving it like that but its incorrect? I dont understand cuz 1+-1 equals 0 and since its multiplacation the answer theoreticly should equal 0 right?

Did you mean for it to be (2+1) or did you mean (2+i)? Clarify that please and then I'd be happy to help!

2+i srry

I got 6 + 12 i.

Wait but its multiplacation..... So it should equal 0 right? Cuz i = Sqrt(-1)

Okay so expanding (1+i)(2+i) we get

2+i+2i+i^2 =

2+3i-1 =

1+3i

Multiplying (1+3i)(3+i) we get

3+i+9i+3i^2 =

3+10i+3(-1) =

10i

Hope that helps!

Wait Oh im so dumbbbb.. YAH I Solved it as i = -1...... Well looks like im kind of dumb.